ACSM's resources for the exercise physiologist a practical guide for health professional.
Organized around the scope of ACSM Exercise Physiologist practice domains, ACSM's Resources for the Exercise Physiologist includes an introductory section focusing on understanding exercise, physical activity, and pre-exercise screening. Coverage of assessment and programming for both healthy and special populations and extensive content about behavior change allow the Exercise Physiologist to provide program options for varying types of clients. Finally, this text covers the ethics, legal issues, and business of fitness managment